1993
DOI: 10.1177/088840649301600306
|View full text |Cite
|
Sign up to set email alerts
|

Supply and Demand of Leadership Personnel in Special Education: A Follow-up Study with Analysis of Failed Searches

Abstract: Concern about the problem of declining numbers of special education doctoral graduates and increasing numbers of faculty vacancies in university training programs has grown since the early 1980s. In this study, we investigated the supply and demand of leadership personnel in special education and communication disorders and extended an existing data base to include the years 1988 to 1992. We also conducted an analysis of failed searches that occurred in 1988, which allowed us to (a) determine the number of ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Smith et al (1988) first discovered that in 1988, only 33% of SE graduates sought faculty positions. In addition, they found that the number of overall graduates had decreased when compared with earlier studies (see Sindelar et al, 1993;Smith & Lovett, 1987). In addition, they found that the number of overall graduates had decreased when compared with earlier studies (see Sindelar et al, 1993;Smith & Lovett, 1987).…”
Section: Reasons For the Demandmentioning
confidence: 75%
See 3 more Smart Citations
“…Smith et al (1988) first discovered that in 1988, only 33% of SE graduates sought faculty positions. In addition, they found that the number of overall graduates had decreased when compared with earlier studies (see Sindelar et al, 1993;Smith & Lovett, 1987). In addition, they found that the number of overall graduates had decreased when compared with earlier studies (see Sindelar et al, 1993;Smith & Lovett, 1987).…”
Section: Reasons For the Demandmentioning
confidence: 75%
“…Notably, only 44% intended to work in academe post graduation. Sindelar and Taylor (1988) and others examining various aspects of the demand for faculty in SE (Dil et al, 1993;Eichinger et al, 2000;Pierce et al, 1992;Pierce & Smith, 1994;Pion et al, 2003;Sindelar et al, 1993;Smith et al, 2001;Smith et al, 2011;Smith & Lovett, 1987;Tyler, et al, 2003) have all approached this line of research guided by the fundamental belief in a free appropriate public education for all students, including those with disabilities, as mandated by Individuals With Disabilities Education Act (IDEA) in 1975 . Pion and her colleagues also found that those in tenure-line faculty positions earned significantly less than their nonacademic counterparts and, due to age and family restrictions, had a low mobility rate.…”
Section: Reasons For the Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…The second type of analysis was a calculation of regression equations for three data categories: APE job openings, fist priority, and second priority. Each equation was calculated using the academic year as the predictor variable and the position opening as the criterion variable (Sindelar, Buck, Carpenter, & Watanabe, 1993;Sindelar & Taylor, 1988). The linear effect of the predictor variable on the criterion variable in a regression equation was tested with an analysis of variance (F test;Moore & McCabe, 1989).…”
Section: Data Analysesmentioning
confidence: 99%